Gynecologic-tract sparing extra peritoneal retrograde radical cystectomy with neobladder - Kulkarni,Jagdeesh N. (2008)
OBJECTIVE: We report on a series of female patients with transitional cell carcinoma of the bladder who underwent extraperitoneal retrograde radical cystectomy sparing the female reproductive organs with neobladder creation. MATERIALS AND METHODS: 14 female patients between the ages of 45 and 72 years who underwent gynecologic-tract sparing cystectomy (GTSC) with neobladder between 1997 and 2002 were retrospectively reviewed. Our surgical technique is also described. Radical cystectomy is accomplished by a retrograde method sparing the uterus, adnexa, vagina and distal urethra. An orthotopic neobladder was constructed using small bowel or sigmoid colon, brought extraperitoneally, and anastomosed to the distal urethra. RESULTS: Operating time ranged from 4.5 to six hours with a mean of 5.3 hours. Ten patients were able to void satisfactorily while four required self-catheterization for complete emptying of the bladder. Seven patients were continent day and night and another 7 reported varying degrees of daytime and nighttime incontinence. One patient died of metastases and another of pelvic recurrence. There were no urethral recurrences. Patient satisfaction with the procedure was high. CONCLUSIONS: Gynecologic-tract sparing cystectomy with orthotopic neobladder is a viable alternative in female patients with muscle invasive traditional cell carcinoma of the bladder, providing oncological safety with improved quality of life. Our extraperitoneal technique, which is an extension of our successful experience with retrograde extraperitoneal radical cystectomy in men, minimizes intraoperative complications and simplifies the management of post-operative morbidity with the neobladder.